Comparing Perioperative Mortality and Morbidity of Minimally Invasive Esophagectomy Versus Open Esophagectomy for Esophageal Cancer: A Nationwide Retrospective Analysis. Issue 2 (25th August 2021) - Sakamoto, Takashi; Fujiogi, Michimasa; Matsui, Hiroki; Fushimi, Kiyohide; Yasunaga, Hideo
Abstract : Objective: We compared the surgical outcomes of minimally invasive esophagectomy (MIE) and open esophagectomy (OE) for esophageal cancer. Summary Background Data: MIE has become a widespread procedure. However, the definitive advantages of MIE over OE at a nationwide level have not been established. Methods: We analyzed patients who underwent esophagectomy for clinical stage 0 to III esophageal cancer from April 2014 to March 2017 using a Japanese inpatient database. We performed propensity score matching to compare in-hospital mortality and morbidities between MIE and OE, accounting for clustering of patients within hospitals. Results: Among 14, 880 patients, propensity matching generated 4572 pairs. MIE was associated with lower incidences of in-hospital mortality (1.2% vs 1.7%, P = 0.048), surgical site infection (1.9% vs 2.6%, P = 0.04), anastomotic leakage (12.8% vs 16.8%, P < 0.001), blood transfusion (21.9% vs 33.8%, P < 0.001), reoperation (8.6% vs 9.9%, P = 0.03), tracheotomy (4.8% vs 6.3%, P = 0.002), and unplanned intubation (6.3% vs 8.4%, P < 0.001); a shorter postoperative length of stay (23 vs 26 days, P < 0.001); higher incidences of vocal cord dysfunction (9.2% vs 7.5%, P < 0.001) and prolonged intubation period after esophagectomy (23.2% vs 19.3%, P < 0.001); and a longer duration of anesthesia (408 vs 363 minutes, P < 0.001). Conclusion: MIE had favorable outcomes in terms of in-hospital mortality, morbidities, and the postoperative hospital stay.